(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
Identifying a person is one of the most important aspects of a medicolegal inquiry. Research has been done to assess stature using various body components. The current study set out to determine whether little finger lengths are a reliable indicator of stature and to compute regression models using the data that were collected. The current study attempted to check the usefulness and calculate the regression models in the estimation of stature from little finger lengths. However, regression equations and multiplication factors are specific to Haryana and nearby regions only. Other parts of India can have some differences in value in comparison to our study. The study was carried out on a cross-sectional sample of 145 adult students from the Haryana region, of which 80 were males and 65 were females. A significant correlation was observed between little finger length and stature, i.e., 0.22 in males and 0.20 in females. The current study’s findings show that little finger lengths are capable of estimating an individual’s stature.